The battle of the Labyrinth Book 4 Percy Jackson and the Olympians - Riordan, Rick (New York Disney Hyperion Books, 2009)
When demonic cheerleaders invade his high school, Percy Jackson hurries to Camp Half Blood, from whence he and his demigod friends set out on a quest through the Labyrinth, while the war between the Olympians and the evil Titan lord Kronos draws near
1
Keywords: ANIMALS, MYTHICAL -- Juvenile fiction; Young adlat -- Fiction